Detection of Different Serotypes of Salmonella enterica in Experimentally Inoculated Equine Fecal Samples by Commercially Available Rapid Tests. (13th October 2014) - Burgess, B.A.; Weller, C.B.; Pabilonia, K.L.; Bolte, D.S.; Van Metre, D.C.; Morley, P.S.
<x xml:space="preserve">Abstract</x> Background Salmonella enterica can significantly impact management of animal facilities. Comprehensive screening is essential for effective control in high‐risk populations. Availability of reliable point‐of‐care diagnostic tests would facilitate these efforts. Hypothesis/Objectives Compare the ability of commercially available rapid diagnostic assays (2 lateral flow immunoassays [LFIs], DNA hybridization [DNAH], real‐time PCR [qPCR]), and culture to detect common serotypes of S. enterica in feces. Animals n/a. Methods In an experimental study, 112 S. enterica isolates were randomly selected from the 10 most common serotypes recovered at a veterinary hospital. Archived isolates were amplified in broth and standardized inocula (100 colony forming units) were incubated with equine feces in tetrathionate broth (TET). Cultures were tested in a blinded fashion by using LFIs, DNAH, qPCR, and culture. Results The LFIs detected 84% and 67% of isolates, respectively, but reactivity varied among serotypes. Both reacted poorly with serotype Cerro (Group K) isolates, and 1 LFI did not react with any serotype Mbandaka (Group C1) or Montevideo (Group C1) isolates. DNAH detected 94% of isolates, whereas culture and qPCR most reliably detected all serotypes. False‐positive results were obtained for 4 negative controls by using DNAH and 1 negative control by using qPCR, but LFIs and culture had no false‐positive results. Conclusions and Clinical Importance Culture, qPCR, and DNAH were effective in detecting most Salmonella isolates, but have limited application at point‐of‐care settings. LFIs are appealing as point‐of‐care tests because of low cost and ease of use, but limited detection of some serotypes needs to be evaluated with samples obtained from naturally infected animals.